2010
DOI: 10.1097/scs.0b013e3181f4aef7
|View full text |Cite
|
Sign up to set email alerts
|

Results of Transmasseteric Anteroparotid Approach for Mandibular Condylar Fractures

Abstract: Management of condylar fractures has been the subject of much disagreement and debate. There is no general consensus for definitive treatment. Although there is a growing tendency for open reduction and internal fixation technique, risks and morbidity of the surgical procedure are still a point of concern for maxillofacial surgeons. To reduce potential complications and improve surgical exposure, the transmasseteric anteroparotid approach was introduced. Since 2008, we have operated on 6 patients (7 fractures)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, low postoperative activity and inadequate functional training may cause trismus. To prevent postoperative contracture of the masseter muscle, several studies have reported that incision of the masseter muscle should be parallel to the muscle bundle [32,46]. Therefore, these techniques should be considered for indications in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, low postoperative activity and inadequate functional training may cause trismus. To prevent postoperative contracture of the masseter muscle, several studies have reported that incision of the masseter muscle should be parallel to the muscle bundle [32,46]. Therefore, these techniques should be considered for indications in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…Potential complications and risks associated with the surgical procedure are still a matter of concern for maxillofacial surgeons. [ 9 ] Visibility and access to the fracture line is sometimes very limited in some of the most commonly followed incisions such as Risdon's submandibular, retromandibular incisions, as they are placed far off from the fracture site, demanding strong soft tissue retraction that can also increase the risk of facial nerve damage ranging from 30% to 48%. [ 10 ] Improper access is the cause for oblique angulation of screw placement that can jeopardize the plate adaptability and stability of fixation.…”
Section: Discussionmentioning
confidence: 99%
“…However, this technique requires the identification of the facial nerve trunk or its branches, at least two at a time, to allow for surgical access between these branches. This requires advanced dissection skills and confidence in the anatomy of the facial nerves in the buccal and mandibular region [10,11]. Despite meticulous dissection, mild neuropraxia can persist up to 13 months postoperatively, and in cases of a transparotid approach, postoperative sialoceles and salivary fistulas can be a nuisance [3].…”
Section: Discussionmentioning
confidence: 99%
“…Although intraoral reduction is generally accepted for symphyseal and parasymphyseal fractures, there is still some debate regarding the use of the intraoral approach to condylar neck and subcondylar fractures because of the surgical skills and associated hardware required [5]. Although various methods of external approaches to the mandible have been proposed, there are no recent articles addressing the classic Risdon approach [6-11]. The authors have used the Risdon approach for open reduction and internal fixation of condylar fractures, in some cases combined with external threaded Kirschner wire fixation and rubber traction.…”
Section: Introductionmentioning
confidence: 99%